2009
DOI: 10.1038/emboj.2009.164
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of p53 and p21 by MKRN1 E3 ligase controls cell cycle arrest and apoptosis

Abstract: Makorin Ring Finger Protein 1 (MKRN1) is a transcriptional co-regulator and an E3 ligase. Here, we show that MKRN1 simultaneously functions as a differentially negative regulator of p53 and p21. In normal conditions, MKRN1 could destabilize both p53 and p21 through ubiquitination and proteasome-dependent degradation. As a result, depletion of MKRN1 induced growth arrest through activation of p53 and p21. Interestingly, MKRN1 used earlier unknown sites, K291 and K292, for p53 ubiquitination and subsequent degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
148
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 69 publications
7
148
0
2
Order By: Relevance
“…The ubiquitylation assay was performed as described previously. 56 Briefly, cells were lysed in 6 M guanidine-HCl buffer (pH 8) containing 5 mM NEM (Sigma-Aldrich), and His-ubiquitin-conjugated proteins were purified by Ni 2+ -NTA (Qiagen, Valencia, CA, USA) and analyzed by western blotting (WB). For ubiquitylation assays using HA-Ub, cells were lysed under denaturing conditions containing 1% SDS.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitylation assay was performed as described previously. 56 Briefly, cells were lysed in 6 M guanidine-HCl buffer (pH 8) containing 5 mM NEM (Sigma-Aldrich), and His-ubiquitin-conjugated proteins were purified by Ni 2+ -NTA (Qiagen, Valencia, CA, USA) and analyzed by western blotting (WB). For ubiquitylation assays using HA-Ub, cells were lysed under denaturing conditions containing 1% SDS.…”
Section: Discussionmentioning
confidence: 99%
“…MKRN1, a protein highly conserved from invertebrates to vertebrates, has a ubiquitous expression pattern in various tissues 25 and functions as an E3 ubiquitin ligase for various substrates 24,26,27 . Previous reports showed that MKRN1 was able to suppress p53 function, and regulate cell growth and apoptosis.…”
Section: Depletion Of Mkrn1 Induces Dr-mediated Extrinsic Apoptosismentioning
confidence: 99%
“…As MKRN1 is an E3 ubiquitin ligase 24,26,27 , we next asked whether MKRN1 E3 ligase activity affected the stability of proteins involved in DISC complexes. When MKRN1 was knocked-down by siRNA or short-hairpin RNA (shRNA), MKRN1 protein was barely detected and MKRN1 messenger RNA levels were reduced up to 70-80% of control mRNAs (Fig.…”
Section: Fadd Ubiquitination and Degradation Is Mkrn1-dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, MKRN1 exhibits divergent functions both in the cell nucleus and the cytoplasm. As an E3 ubiquitin ligase it acts on itself and the catalytic subunit of human telomerase reverse transcriptase (26), p53 and p21 (27). Furthermore, MKRN1 modulates RNA polymerase II-mediated transcription (28) and may play a role in mRNA decay (29).…”
mentioning
confidence: 99%